A Study On Aerodynamic Shape of Fin of Model Rocket using Computational Fluid Dynamics (CFD) - Mohammad Hisham Shahir bin Noor Azman (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The design of the model rocket can affect the model during flight, such as a model will wobble. The model rocket also consists the rocket fins at the bottom of the rocket to provide stability during flight. To avoid the wobble rocket, they must choose the correct shape of the fin. Furthermore, the comparison of the shape of the fin able to generate more lift force was investigated in this study. Therefore, this study has been carried out in the computational fluid dynamics (CFD) simulation using ANSYS Fluent. To carry out the simulation, varies 3D shape of the fin has been generated such as rectangle, clipped delta and trapezoid. Then, these 3D shape of the fin has been going through the meshing process. After that, setup the boundary conditions in the ANSYS Fluent. By the end of the simulation, rectangle shows the highest lift coefficient and drag coefficient among the others despite the trapezoid shape has the lowest pressure distribution at upper surface of air foil. In conclusion, this is shown the rectangle shape of the fin has the highest lift force generated and make the rocket can flight to the higher altitude.